Electromagnetic multipole of positive and negative parity states in 24Mg by elastic and inelastic electron scattering - Manie, NOORI S.; Alzubadi, Ali A. (Iraqi Journal of Physics, 2019)
In the present work, the nuclear shell model with Hartree–Fock (HF) calculations have been used to investigate the nuclear structure of 24Mg nucleus. Particularly, elastic and inelastic electron scattering form factors and transition probabilities have been calculated for low-lying positive and negative states. The sd and sdpf shell model spaces have been used to calculate the one-body density matrix elements (OBDM) for positive and negative parity states respectively. Skyrme-Hartree-Fock (SHF) with different parameterizations has been tested with shell model calculation as a single particle potential for reproducing the experimental data along with a harmonic oscillator (HO) and Woods-Saxon (WS) single-particle potentials. The effect of the nuclear effective charge has been implemented via using different folding models; valance, Tassie and Bohr-Mottelson. The evaluated results have been discussed and compared with available experimental data.